High virulence does not necessarily impede viral adaptation to a new host: a case study using a plant RNA virus. Issue 1 (December 2017) - Willemsen, Anouk; Zwart, Mark; Elena, Santiago
Abstract Background Theory suggests that high virulence could hinder between-host transmission of microparasites, and that virulence therefore will evolve to lower levels. Alternatively, highly virulent microparasites could also curtail host development, thereby limiting both the host resources available to them and their own within-host effective population size. In this case, high virulence might restrain the mutation supply rate and increase the strength with which genetic drift acts on microparasite populations. Thereby, this alternative explanation limits the microparasites' potential to adapt to the host and ultimately the ability to evolve lower virulence. As a first exploration of this hypothesis, we evolvedTobacco etch virus carrying an eGFP fluorescent marker in two semi-permissive host species, Nicotiana benthamiana andDatura stramonium, for which it has a large difference in virulence. We compared the results to those previously obtained in the natural host, Nicotiana tabacum, where we have shown that carriage ofeGFP has a high fitness cost and its loss serves as a real-time indicator of adaptation. Results After over half a year of evolution, we sequenced the genomes of the evolved lineages and measured their fitness. During the evolution experiment, marker loss leading to viable virus variants was only observed in one lineage of the host for which the virus has low virulence, D. stramonium . This result was consistent with the observation that there was a fitness cost ofeGFP in this host, while surprisingly no fitness cost was observed in the host for which the virus has high virulence, N. benthamiana . Furthermore, in both hosts we observed increases in viral fitness in few lineages, and host-specific convergent evolution at the genomic level was only found inN. benthamiana . Conclusions The results of this study do not lend support to the hypothesis that high virulence impedes microparasites' evolution. Rather, they exemplify that jumps between host species can be game changers for evolutionary dynamics. When considering the evolution of genome architecture, host species jumps might play a very important role, by allowing evolutionary intermediates to be competitive.